Implementasi Strategis Sistem Informasi Akuntansi Melalui Analisis Komparatif - Adinda Dwi Arini (Jurnal Riset Akuntansi, 2024)
This research aims to investigate the strategic implementation of accounting information systems (AIS) through a comparative analysis of various approaches employed within organizations. In the face of rapidly changing business dynamics, the role of AIS is pivotal in supporting accurate managerial decisions and ensuring operational sustainability.The research methodology involves data collection from multiple organizations that implement AIS using distinct approaches. A comparative analysis is conducted across various implementation aspects, including system design, technological integration, data management, information security, and their impacts on financial and operational performance within the companies. The findings reveal that a strategic approach in implementing AIS provides a competitive edge for organizations. It was identified that factors such as appropriate technology selection, efficient integration, robust data security, and integrated management significantly contribute to the success of AIS implementation.These findings offer valuable insights for practitioners and managers in planning, developing, and enhancing the effectiveness of AIS in the context of dynamic market changes and business environments. The implications of this research provide a foundation for organizations to make strategic decisions regarding AIS investments and implementation to enhance their competitiveness and operational performance.